Development of a psychological health promotion intervention for ultra-orthodox Jewish mothers of children with ADHD using the intervention mapping protocol - Jennifer R. Budman; Adina Maeir (BMC, 2024)
Abstract Background Attention Deficit Hyperactivity Disorder (ADHD) is a common neuro-developmental health condition in children and adolescents, in which its associated behavior manifestations are known to negatively affect members of the family unit, especially mothers. Ultra-orthodox Jewish (UOJ) community is growing globally and mothers of children with ADHD in this community are potentially at risk for negative health outcomes. As the UOJ community is culturally conservative, maintaining a distinct separation from outside influences, they often avoid utilizing public mental health services due to stigma and a lack of culturally sensitive treatments. Thus, this study aimed to develop a theory-driven and culturally appropriate psychological health promotion intervention for these mothers using the Intervention Mapping protocol. Methods A mixed-method design was used. Qualitative content analysis was performed on four focus groups (n=25). Additionally, descriptive statistics including the content validity index was used to measure feedback regarding the developed intervention protocol's relevance, effectiveness, and appropriateness Theoretical models for behavior change, including the Behavior Change Wheel's COM-B system and the Theoretical Domains Framework, and literature on ADHD in the general population and the ultra-orthodox community were integrated in the process. Intervention components were systematically derived from findings. Results Key determinants of health behavior change were identified, resulting in formulating intervention objectives addressing stigma reduction surrounding ADHD, increasing knowledge about the ADHD condition and treatment, awareness of the school systems' capabilities in meeting the ADHD child's needs, enhancing mothers' advocacy skills, and maternal self-care. Intervention? strategies included a group setting, providing information on health consequences, social support, re-attribution, active learning, goal setting, and promoting an identity associated with the desired behavior change. Mothers' quantitative feedback confirmed the overall relevance, effectiveness, and appropriateness of the interventions' content (CVIavg= .86, .85, .87). Conclusions Intervention Mapping facilitated the development of a culturally sensitive psychological health promotion intervention for ultra-orthodox Jewish mothers of children with ADHD. Further research is warranted to assess intervention feasibility and effectiveness.